Konsep Pendidikan Al Ghozali dan Pengembangan Kebudayaan Religius - Muhammad Fat Hurroziqy; Ita Rodiah (CV. Ulil Albab Corp, 2023)
Education in Islamic boarding schools studies the yellow book by Al-Ghozali such as Bidayatul Hidayah, Ihya 'Ulumuddin, and Ayyuhal Walad in its contents there is a chapter that discusses the world of education, in the book it is also explained about religiosity as well. The purpose of writing this article is to find out how far the application of Al-Ghozali's thinking in the world of schools based on pesantren and how the process of creating a culture of religiosity in schools based on pesantren. The method used is a literature review and is supported by in-depth observations and interviews at a boarding school based in Tulungagung which teaches Al-Ghozali's books and applies religious culture to its students. The results of these findings are the development of a culture of religiosity in this pesantren is based on the teachings of tazkiah al-nafs in Al-Ghozali's first book of Ihya' al ulumuddin, namely worship such as praying in congregation, praying sunnah, thinking and praying as well as other practices such as tahlil, istighosah, and manakiban. The second is the concept of muamalah, namely providing support to friends, paying attention to friends who are sick and doing community service. The third is morals, namely shaking hands, speaking well, politeness, respecting others.